Test for Vigabatrin-Induced Field Defects in Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
A visual-evoked potential (VEP) technique for identifying visual field defects in children with epilepsy treated with vigabatrin has been developed at Aston University, Birmingham, and Cardiff University, UK.